Optimization Design and Hydrodinamic Test on Propeller Mini Submarine - Asrowibowo, Nurwidhi; Indiaryanto, Mahendra; , Rina (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
The defense equipment technology development which is in this case is the submarine research became an important subject and need to be further researched. One part of it is, designing driving components (propeller) of a mini-submarine with a high level of efficiency. Test models of mini-submarines of 22 m was used as a basis for developing propeller through scale models with the scale factor of 1:7. Expected propeller design optimization is capable of producing high effisensi currently working on the operational speed propeller. This research method is based on the results of the propeller design optimization, numerical simulations using Computer Fluid Dynamic (CFD ) and hydrodynamic test. The results of this study shows that the method applied here could provide a solution in the choice of an efficient propeller designs for mini-submarines 22 m.